1990
DOI: 10.1017/s002211209000129x
|View full text |Cite
|
Sign up to set email alerts
|

Steady two-dimensional flow through a row of normal flat plates

Abstract: A numerical and experimental study is described for the two-dimensional steady flow through a uniform cascade of normal flat plates. The Navier–Stokes equations are written in terms of the stream function and vorticity and are solved using a second-order-accurate finite-difference scheme which is based on a modified procedure to preserve accuracy and iterative convergence at higher Reynolds numbers. The upstream and downstream boundary conditions are discussed and an asymptotic solution is employed both upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Numerical solutions for circular cylinder cascades have been presented by Fornberg (1991) (with Re 6 400 in the present terms and 5 6 H 6 100) and, very recently and to much higher Reynolds numbers, by Gajjar & Azzam (2004). Similar computations for flat-plate cascades have been by presented by Natarajan, Fornberg & Acrivos (1993) (with Re 6 400 and 5 6 H 6 25) and Ingham, Tang & Morton (1990) (with Re 6 500 and H = 2). Chernyshenko's (1988) asymptotic theory was extended to the cascade case by Chernyshenko & Castro (1993) and numerical computations gave results which were shown to tend qualitatively towards those expected, but only at the very highest Reynolds numbers.…”
Section: Introductionsupporting
confidence: 56%
“…Numerical solutions for circular cylinder cascades have been presented by Fornberg (1991) (with Re 6 400 in the present terms and 5 6 H 6 100) and, very recently and to much higher Reynolds numbers, by Gajjar & Azzam (2004). Similar computations for flat-plate cascades have been by presented by Natarajan, Fornberg & Acrivos (1993) (with Re 6 400 and 5 6 H 6 25) and Ingham, Tang & Morton (1990) (with Re 6 500 and H = 2). Chernyshenko's (1988) asymptotic theory was extended to the cascade case by Chernyshenko & Castro (1993) and numerical computations gave results which were shown to tend qualitatively towards those expected, but only at the very highest Reynolds numbers.…”
Section: Introductionsupporting
confidence: 56%
“…As an alternative to the least-square matching, the exact matching strategy, which solves the same number of matching equations as the coe cients, namely n = m+1 in Equation (22), were applied in References [17,19]. Nevertheless, we found that this method is not robust since the convergence speed and the results can be very sensitive to the matching locations.…”
Section: Combined Analytical-numerical Methodsmentioning
confidence: 99%
“…This method was applied to treat the stress singularity in die swell problems in Stokes ows [6,7,18]. Several studies [17,19,20] have employed the local asymptotic solution for the Stokes ow to overcome the vorticity singularity in the numerical solution of the NavierStokes equations adopting the stream function-vorticity formulation. They assigned the local asymptotic solution for the Stokes ow in the neighbourhood of an angular point as the boundary condition for the ow in the remaining region, which was solved using a ÿnite-di erence scheme.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations